Pengembangan Penilaian Menulis Guru Bahasa Indonesia dengan Melibatkan Self Esteem - Sukenti, Desi; Tambak, Syahraini; Sabila, Nur (UIR Press, 2025)
This study aims to analyze the development of Indonesian language teachers' writing assessments involving self-esteem. This study uses a quantitative approach with an ex post facto design. The sample used was Indonesian language high school teachers, both public and private teachers in Pekanbaru City, Riau, Indonesia. The research sample used was 52 Indonesian language teachers. The data collection technique used was a questionnaire. The measurement design of this research instrument was carried out using a Likert scale. Data were analyzed using descriptive statistics for variable levels and inferential statistics for requirement tests. A model equation structure test was conducted by evaluating the measurement model (outer model). The results showed that there was a direct effect of self-esteem on the writing assessment of Indonesian language teachers in Pekanbaru, Riau, Indonesia of 62%. This illustrates that strengthening the affective mental aspect is prioritized and considered in assessing the learning process, this is useful as affective feedback or self-evaluation. The findings revealed that writing assessments involving high self-esteem have a positive impact, thus increasing self-confidence in assessing and growing self-confidence. This makes self-esteem an important aspect of self-esteem to have for Indonesian language teachers.